Birthweight predicts glomerular filtration rate in adult-life: population based cross sectional study. Issue 1 (1st January 2021) - Al Salmi, Issa; Hannawi, Suad
Abstract: Introduction: Worldwide, there is a global progressive rise of chronic kidney disease. In parallel, children born after intra-uterine growth retardation are surviving to adult-life and beyond. This study describes the association of birthweight with and estimated glomerular filtration rate (eGFR). Methods: Australian Diabetes, Obesity and Lifestyle (AusDiab) study participants were asked to complete a birthweight questionnaire. The associations between birthweight and eGFR were determined. Results: A total of 4502 reported information related to their birthweight, with the other responders did not provide a value. The birthweight of the participants ranged from 0.4 to 7.0 kg with a mean-(SD) of 3.37 (0.7) kg. The mean (95%CI) birthweight was lower for females, 3.28 (0.6) kg, when compared to males, 3.5 (0.7) kg. Eight percent had a birthweight less than 2.5 kg. The eGFR was strongly and positively associated with birthweight, with people in the lowest sex-specific birthweight-quintiles having the lowest mean eGFR. This relationship persisted with adjustment for confounding factors. The OR(CI) for eGFR <10th-percentile (<61.4 ml/min for females and <73.4 for males) for people in the lowest vs. the higher birthweight-quintile was 2.19 (95%CI 1.14–4.2) for females and 2.37 (1.1–5.3) for males, after adjustment for other factors. Conclusions: Birthweight had a positive relationship with eGFR. Possible explanations include an association of birthweight with nephron-endowment. From a global health perspective but more in developing countries and in populations in epidemiologic transition, where substantially lower birthweights coexist with recently improved infant and adult survivals, the overall impact of this phenomenon on the population health profile could be more substantial.